2000
DOI: 10.1007/s004390000323
|View full text |Cite
|
Sign up to set email alerts
|

Porphobilinogen deaminase gene in African and Afro-Caribbean ethnic groups: mutations causing acute intermittent porphyria and specific intragenic polymorphisms

Abstract: Acute intermittent porphyria (AIP), the most common acute hepatic porphyria, is a low-penetrant autosomal dominant disorder caused by mutations in the porphobilinogen deaminase (PBGD) or hydroxymethylbilane synthase (HMBS) gene. Although AIP has been identified in all the main ethnic groups, little is known about PBGD gene defects in Africans, Afro-Caribbean and Afro-Americans. We have carried out PBGD gene screening among seven unrelated AIP families and 98 controls belonging to the Afro-Caribbean (French Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…A study of seven West and North African and Afro-Caribbean patients with AIP characterised six different mutations, four of which were novel 41. In this study, three of the four novel mutations were found in Black or mixed ancestry patients.…”
Section: Discussionmentioning
confidence: 69%
“…A study of seven West and North African and Afro-Caribbean patients with AIP characterised six different mutations, four of which were novel 41. In this study, three of the four novel mutations were found in Black or mixed ancestry patients.…”
Section: Discussionmentioning
confidence: 69%
“…Single-nucleotide polymorphism (SNP) analysis: Eight SNPs in the PBGD gene, namely 64C/T, 1345A/G, 2479A/G, 3581A/G, 3982C/T, 6479G/T, 7064C/A and 8578G/A, were analysed in all members of the six AIP families (Robreau-Fraolini et al 2000). Except for SNP 3982C/T, methods for determination of the other seven SNPs have been described previously .…”
Section: Methodsmentioning
confidence: 99%
“…Of the 14 known SNPs in the PBGD gene, seven were selected for their high heterozygosities (table 2) [13]. Intragenic haplotypes of the seven SNPs cover the PBGD gene of 8.6 kb, starting at position -64 in the promoter region and ending at position 8578 in the 3)-UTR.…”
Section: Discussionmentioning
confidence: 99%
“…In Great Britain, about 3% of all AIP index cases may have de novo mutations and in France, the rate of de novo mutations was estimated to be 2% [8,12]. In addition to mutations, a total of 16 intragenic single nucleotide polymorphisms (SNPs) have been identified in the PBGD gene, two of which were only observed among the African and AfroCaribbean populations [13].…”
Section: Introductionmentioning
confidence: 99%